Bioinformatic and cell-based tools for pooled CRISPR knockout screening in mosquitos - Raghuvir Viswanatha; Enzo Mameli; Jonathan Rodiger; Pierre Merckaert; Fabiana Feitosa-Suntheimer; Tonya M. Colpitts; Stephanie E. Mohr; Yanhui Hu; Norbert Perrimon (Nature Communications, 2021)
Forward genetic approaches such as CRISPR screens are powerful ways to identify essential genes and those that influence host-pathogen interactions. Here the authors design a bioinformatics portal for sgRNA design and a recombination-mediated cassette system for delivery into mosquito cell lines.